Ethnography and prostitution in Peru - Nencel, Lorraine (London ; Sterling, Va. : Pluto Press, 2001)
"A feminist study of prostitution in Peru, this book interrogates the ways in which sexuality, gender and illicit behaviour have been constructed (and deconstructed) over the years. Lorraine Nencel deals with issues such as AIDS, machismo and the regulation of the sex trade. She analyses the question of whether sex workers are victims or agents of control."--Jacket
Introduction: zooming in on the locality -- pt. 1. (En)gendered enclosures -- Historical narrative of prostitution -- Read all about it : gender meanings and the written press -- Prostitution and the construction of men's sexual selves -- pt. 2. Day and night -- Writing up the rhythm of fieldwork: an introduction to part II -- Shaping identities in first encounters -- Between the stove and the kitchen table -- Fusion of truths into illusions : the night life and street prostitution -- Between the four walls : embodying and enacting the prostitute -- Gendered enclosures and gender identities.
Includes bibliographical references (pages 239-244) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Prostitution -- Peru; Women -- Peru -- Social conditions; Femmes -- Pérou -- Conditions sociales; PSYCHOLOGY -- Human Sexuality; SELF-HELP -- Sexual Instruction; SOCIAL SCIENCE -- Gender Studies; Prostitution; Women -- Social conditions; Peru; Prostitutie